Repeated blood sampling from an adult Danio Rerio - Eissa, Manar; Abdullah, Raihan; Sharif, Faez; Mohd Nasir, Mohd Hamzah (CRC Press, 2024)
Zebrafish (Danio rerio) has emerged as an enormously powerful and popular model for biomedical and preclinical research over the past few years. This is largely attributed to the significant genetics and physiological homology with higher vertebrates, especially humans, and the emerging opportunities for genetic manipulation and live in vivo imaging. Furthermore, the body fluids of zebrafish, including blood, plasma, and interstitial and cerebrospinal fluids, can also provide an insightful data on health and disease status. The high similarity between zebrafish and human plasma proteins makes zebrafish an excellent alternative model organism for studying hematologic and metabolic diseases in the quest for a new therapy. The analysis of the metabolites and the blood parameters of zebrafish is essential, as it might provide important details about the physiological condition of the fish. Besides, the longitudinal analysis of individual zebrafish provides a better insight of metabolic dynamics than the single point blood analysis.